Meta-emotion philosophy pada Guru PAUD : Strategi dan Keyakinan terkait Sosialisasi Emosi - Mafaza Mafaza; Septi Mayang Sarry (UNS Press, 2025)
Early childhood needs adults to play the role of developing their emotional abilities. This present study investigated the socialization of emotions process by pre-school teachers through meta-emotion philosophy (an approach to teacher’s own emotion and to their student’s), first: to describe the emotional socialization style of Early Childhood Education teachers, second: to examine the significance of belief (regarding regulation, awareness, acceptance of teacher’s own emotion and to their student’s) towards emotional socialization styles. Participants were 175 pre-school teachers (Mage = 40 years), recruited from 28 kindergartens in Padang City. The measuring instrument used in this study is the Crèche Educator Emotional Styles Questionnaire. The results showed that teachers used both styles of emotional socialization, especially the dismissing style, more frequently than coaching. Furthermore, teacher emotional efficacy (related to student emotions and personal emotions) was found to simultaneously influence both emotional socialization styles. Teachers' beliefs as emotional socializers have a greater effective contribution than efficacy related to personal emotions. Meanwhile, denial of personal emotions does not affect emotional socialization styles. In addition, no differences were found in teachers' emotional socialization styles based on having/not having children, teaching experiences, and educational background